FORECASTING SUNFLOWER SEEDS AND OIL PRODUCTION IN KAZAKHSTAN USING REGRESSION AND TIME SERIES MODELS - Idrisheva, Azhar (Nazarbayev University School of Sciences and Humanities, 2025)
Kazakhstan is considered a major global producer of sunflower seeds, ranking among top 10 countries worldwide. Sunflower cultivation and sunflower oil production experience a rapid growth in the country, holding a potential to greatly benefit the country’s economic and agricultural sectors. This capstone project aims to develop statistical models to predict sunflower yields and sunflower oil production until the year 2035. Using historical data, the project uses regression and time series analysis to identify patterns and impact of variables. By leveraging these findings, the project aims to support effective decision-making in agricultural sector to improve sustainable practices and enabling the effective scaling of sunflower production in Kazakhstan.
Keywords: type of access: open access; Crop Yield Prediction; Statistical Modeling; Kazakhstan Agriculture; Time Series Analysis; Sunflower Production; Sunflower Oil Production; Data Analysis